2018
DOI: 10.3390/nano8040238
|View full text |Cite
|
Sign up to set email alerts
|

Controlled Synthesis of Cu and Cu2O NPs and Incorporation of Octahedral Cu2O NPs in Cellulose II Films

Abstract: In this study, Cu and Cu2O nanoparticles (NPs) were synthesized through chemical reduction of soluble copper-chelating ligand complexes using formaldehyde as a reducing agent. The influence of various chelating ligands, such as ethylenediaminetetraacetic acid (EDTA), diethylenetriaminepentaacetic acid (DTPA), and a surface-active derivative of DTPA (C12-DTPA), as well as surfactants (i.e., hexadecyltrimethylammonium bromide (CTAB), dodecyltrimethylammonium chloride (DoTAC), sodium dodecyl sulfate (SDS), and di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…As per the reported literature scalable route to prepare hybrid materials could be applied for enhancing the sensitivity of sensors for various applications. 30 One of the low-cost solutions to prepare smart 3D printed sensors for bio-medical applications lies in the fabrication of programmable feedstock filaments. Some studies have been reported on the use of smart sensors for non-enzymatic glucose sensing applications.…”
Section: Introductionmentioning
confidence: 99%
“…As per the reported literature scalable route to prepare hybrid materials could be applied for enhancing the sensitivity of sensors for various applications. 30 One of the low-cost solutions to prepare smart 3D printed sensors for bio-medical applications lies in the fabrication of programmable feedstock filaments. Some studies have been reported on the use of smart sensors for non-enzymatic glucose sensing applications.…”
Section: Introductionmentioning
confidence: 99%
“…Among various practical approaches to preparing Cu 2 O-Cu nanoparticles, the chemical reduction approach is considered a straightforward, affordable, and scalable technique [12]. Although the preparation of Cu 2 O-Cu nanoparticles has advanced significantly, this technique only works at low copper ion concentrations (<1,000 mg.l −1 ).…”
Section: Introductionmentioning
confidence: 99%